ANUL JUBILIAR CA PROTECȚIE A DREPTURILOR OMULUI ÎN SITUAȚII DE CRIZĂ ECONOMICĂ. LEVITIC 25 ÎN TEOLOGIA BIBLICĂ ȘI ÎN PREZENT (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The Jubilee as Protection of Human Rights in Situations of Economic Crisis. Leviticus 25 in Biblical Theology and in the Present.This article discusses the issue of economic crises and their impact on the economic marginalized people. The perspective that we will adopt is that of biblical theology, that is, we will trace the biblical concept of Jubilee through all the stages of redemptive history—creation, fall, Israel, prophets, Jesus, church, eschaton—in order to show how God cares for the economic wellbeing of all people and that he provides solutions in order for people to survive economic crises. The Jubilee, as our study will show, was anchored in creation and had an eschatological orientation. On the one hand, Jubilee represented a return to Eden, an idealized world, where all people enjoyed economic blessings. On the other hand, Jubilee, as interpreted by the prophets, anticipated an eschatological world, brought about by Messiah. Thus, at his first coming, Christ inaugurated the fulfillment of Jubilee, both in its economic as well as spiritual dimenssion, emphasizing the latter, and thus pointing forward to its complete and permanent fulfillemnt at his second coming, especially in its economic dimension. In the meantime, the Church is called to implement both these dimensions in her communal life.